A modified piecewise linear constant life diagram for fatigue life prediction of carbon fiber/polymer multidirectional laminates. Issue 2 (30th November 2022) - Behera, Alok; Thawre, Manjusha M.; Ballal, Atul; Manjunatha, CM; Krishnakumar, Dinesh; Chandankhede, Shardul
Abstract: Prediction accuracy of constant life diagrams (CLDs) for fiber‐reinforced plastics varies with the stacking, tensile/compression dominated failure, input S–N curves, the complexity of the plot, and so forth. The article's authors propose a modified piecewise linear CLD and compare its prediction accuracy with traditional piecewise and 2‐segment anisomorphic CLD. The constant amplitude fatigue life data for three different carbon fiber reinforced polymer composites multidirectional laminates that is (+45, −45, +45, and −45)2S, (+45, −45, 0, and 90)2S, and (0, 90, 0, and 90)2S were generated at five different stress ratios ( R = σ min / σ max ) that is, R = 0.1 and 0.5 (T–T), −1 and critical stress ratio (T–C), and 5 (C–C). The proposed modified Piecewise linear CLD considers the critical stress ratio (UCS/UTS) as a definite input node. The prediction accuracy of the proposed CLD and others was evaluated using additional fatigue testing at random stress ratios and stress levels. The proposed CLD showed the highest prediction accuracy compared to Piecewise or Anisomorphic CLD. The non‐linear CLD plotted using single S‐N curve data may save time and effort but achieving absolute accuracy will ultimately depend on the stacking sequence. Abstract :